8B.08: SUSTAINED BENEFICIAL EFFECTS OF MULTI-ELECTRODE RENAL DENERVATION ON CARDIAC ADAPTATIONS IN RESISTANT HYPERTENSION. (June 2015) - Tsioufis, C.; Papademetriou, V.; Dimitriadis, K.; Kasiakogias, A.; Kordalis, A.; Thomopoulos, K.; Tsiachris, D.; Milkas, A.; Kefala, A.; Tousoulis, D.
Abstract : Objective: In this study we investigated whether multi-electrode catheter-based renal sympathetic denervation (RDN) has favorable effects on left ventricular (LV) structural and functional indices in patients with resistant hypertension after a follow-up of 24 months. Design and method: Twenty patients with resistant hypertension [age: 57 ± 10 years, 13 males, office blood pressure (BP): 182/97 ± 19/18 mmHg under 4.5 ± 0.6 drugs] who underwent RDN were followed-up for 24 months. A full transthoracic echocardiographic study was performed in all patients and LV mass was calculated using the Devereux formula and was indexed for body surface area and height. Results: Average office BP was reduced to 148 ± 21/85 ± 14 mmHg at 12 months and to 143 ± 23/80 ± 14 mmHg at 24 months (p < 0.001 for all). In the RDN group, LV mass index was significantly reduced from 136 ± 20.1 g/m2 (56.5 ± 8.7 g/m2.7) to 121 ± 16.6 g/m2 (50.6 ± 6 g/m2.7) at 12 months and to 115.6 ± 23.3 g/m2 (48.8 ± 9.3 g/m2.7) at 24 months (p < 0.01 for all). RDN decreased mean interventricular septum thickness from 12.1 ± 1.2 mm to 11.4 ± 0.9 mm at 12 months and to 11.3 ± 0.9 mm at 24 months (p < 0.05 for all). After RDN, the number of patients with concentric LV hypertrophy (i.e. relative wall thickness > 0.42 and LV mass > 48 g/m2.7 for male and > 44 g/m2.7 for female) decreased from 16 patients (80%) at baseline to 10 patients (50%) at 12 months, and to 7 patients (36.8%) at 24 months. Regarding diastolic function RDN caused an increase in mitral valve É / Á ratio from 0.62 ± 0.28 to 0.70 ± 0.25 at 12 months and to 0.84 ± 0.32 at 24 months (p < 0.05 for all) and a decrease in the E / É ratio from 14.8 ± 6.1 to 11.8 ± 3.7 at 12 months and to 9.7 ± 4 (p < 0.05 for all). Conclusions: This the first study to show that multi-electrode RDN system results in a significant and sustained improvement of diastolic function and attenuation of LV mass index in increased cardiovascular risk resistant hypertensive patients after a follow-up of 24 months. These results suggest pleiotropic cardiovascular benefits of RDN therapy in the setting of resistant hypertension.